Efeito de cenários climáticos e de uso e cobertura da terra futuros nos processos hidrossedimentológicos: o caso da bacia do Rio Taperoá – estado da Paraiba - Silva, Leonardo Pereira e (2019)
Anthropogenic actions on land cover and climate variability are the controlling factors of the environment, these factors are even more impacting in the semi-arid region of Brazil, which is characterized by high spatial-temporal variability of precipitation and high values of evapotranspiration. This study aimed to analyze the influence of pessimistic and optimistic future climate scenarios on hydrosedimentological processes for the Taperoá River basin in the period between 2046 and 2064. Initially, the study identified changes in land use and cover in the Taperoá River basin. in the years 1990, 1999 and 2002, and then estimated the land cover for the year 2060 using the LCM model through the RNMLP dynamic modeling algorithm. The pessimistic and optimistic future climate scenarios were estimated using atmospheric global circulation models CNRM-CM3 and MIROC3.2. The study also performed hydrosedimentological modeling to estimate the flow and production of future sediments using the SWAT model and future land cover based on RNMLP. The main changes in land use and land cover in 2002 when compared to 1990 was the decrease in the class of arboreal shrubby vegetation to shrubby vegetation, this behavior was observed mainly in the eastern portion of the basin. Dynamic modeling using the RNMLP showed satisfactory results for the Taperoá River basin with an accuracy of 89.69% and a Kappa index of 0.61. The scenario foreseen for 2060 showed an increase in the area occupied by the herbaceous shrub vegetation class (38%) and a decrease in the shrubby arboreal vegetation class (2.95%). The flow results obtained for calibration and validation show that the SWAT overestimated the average flow observed, however it presented satisfactory results of R² and Nash of 0.85 and 0.82 for the calibration and 0.90 and -0.02 for the validation, respectively. The results presented showed a great variability of sediment production estimated by climate models. The results showed that the CNRM-CM3 model in the pessimistic scenario estimated at 22.74 ton/ha/year, while the MIROC3.2 model in the pessimistic scenario, the sediment production was 5.36 ton/ha/year. Thus, it can be concluded that the choice of the chosen model, added to the uncertainties in land use and cover, greatly influence the results of flow and sediment production in the region.